ALGORITHM DEVELOPMENT OF SATELLITE IMAGE PROCESSING TO DETECT THE CONCENTRATION OF SUSPENDED PARTICULATE MATTER IN COASTAL WATERS OF RED RIVER DELTA - Thao, Nguyen Van; Vinh, Vu Duy; Ve, Nguyen Dac; Canh, Pham Xuan (Vietnam Journal of Marine Science and Technology, 2016)
In this research, a set of optical data measured in the coastal waters of Red River Delta is used to develop the empirical algorithm for detecting the concentration of suspended particulate matter (SPM). The result of the study shows that the relationship between water-leaving reflectance and the concentration of SPM follows polynomial function with correlative coefficient (R2) > 0.9. Landsat-8 OLI and VNREDSAT-1 satellite images were used to apply this algorithm for detecting the concentration of SPM in the coastal waters of Red River Delta. The concentrations of SPM from image processing and numerical model are much close to each other. The study result will be a valuable reference for studying on water quality in coastal area from remote sensing.